Analiza mamograma - Hertl, Kristijana (Radiology and oncology (Ljubljana), 1998)
Mammography is radiography of the breast. It is an important tool in the detection of small tumors which cannot be clinically detected by palpitation. The mammogram appearance of such small carcinomas is often very atypical; indistinct symptoms of malignancy can easily be overlooked if the mammogram is carelessly and unsystematically analyzed and technically inappropriate. It is therefore very important to know how a healthy breast looks like, in order to be detect the differences that are suspicious.
Keywords: Breast neoplasms; diagnostika; dojke; Mammography; mamografija; rak (medicina)